The molecular chaperone TRAP1 in cancer: From the basics of biology to pharmacological targeting. (November 2021) - Masgras, Ionica; Laquatra, Claudio; Cannino, Giuseppe; Serapian, Stefano A.; Colombo, Giorgio; Rasola, Andrea
Abstract: TRAP1, the mitochondrial component of the Hsp90 family of molecular chaperones, displays important bioenergetic and proteostatic functions. In tumor cells, TRAP1 contributes to shape metabolism, dynamically tuning it with the changing environmental conditions, and to shield from noxious insults. Hence, TRAP1 activity has profound effects on the capability of neoplastic cells to evolve towards more malignant phenotypes. Here, we discuss our knowledge on the biochemical functions of TRAP1 in the context of a growing tumor mass, and we analyze the possibility of targeting its chaperone functions for developing novel anti-neoplastic approaches.